Synthesis of the novel series of bispyridinium compounds bearing (E)-but-2-ene linker and evaluation of their reactivation activity against chlorpyrifos-inhibited acetylcholinesterase - Musilek, Kamil; Kuca, Kamil; Jun, Daniel; Dohnal, Vlastimil; Dolezal, Martin (Bioorganic & medicinal chemistry letters, 2006)
Six potential AChE reactivators were synthesized using modification of currently known synthetic pathways. Their potency to reactivate AChE inhibited by insecticide chlorpyrifos was tested in vitro. According to the results, (E)-1-(2-hydroxyiminomethylpyridinium)-4-(4-hydroxyiminomethylpyridinium)-but-2-ene dibromide seems to be the most potent AChE reactivator. The reactivation potency of these compounds depends on structural factors such as constitution of the linking chain between both pyridinium rings, position of the oxime moiety at the pyridinium ring and presence of quaternary nitrogens.
Keywords: Cholinesterase Inhibitors; Nitrogen; vztah mezi dávkou a účinkem léčiva; Oximes; dursban; acetylcholinesterasa; Cholinesterase Reactivators; Pyridinium Compounds; krysa rodu Rattus; Hydrocarbons, Brominated; Animals; pyridinové sloučeniny; bromované uhlovodíky; zvířata; Rats; dusík; reaktivátory cholinesterasy; oximy; Acetylcholinesterase; cholinesterasové inhibitory; Dose-Response Relationship, Drug; Chlorpyrifos